Randomized controlled study of the T‐type calcium channel antagonist MK‐8998 for the treatment of acute psychosis in patients with schizophrenia. (27th March 2013) - Egan, Michael F.; Zhao, Xin; Smith, Andrew; Troyer, Matthew D.; Uebele, Victor N.; Pidkorytov, Valerii; Cox, Kevin; Murphy, Michael; Snavely, Duane; Lines, Christopher; Michelson, David
Abstract : Objective: This study aimed to evaluate whether the T‐type calcium channel antagonist MK‐8998 was effective in treating acute psychosis in patients with schizophrenia. Methods: This was a randomized, double‐blind, parallel‐group study. After a placebo lead‐in, acutely psychotic inpatients with schizophrenia were randomized to 4 weeks of MK‐8998 12/16 mg daily ( N = 86), olanzapine 10/15 mg daily ( N = 47), or placebo ( N = 83). The primary efficacy measure was score on the Positive and Negative Syndrome Scale (PANSS). Results: Out of 216 randomized patients, 158 completed the 4‐week study: MK‐8998 = 58 (67.4%), olanzapine = 38 (80.9%), and placebo = 62 (74.7%). The mean changes from baseline in PANSS score at week 4 for MK‐8998 and olanzapine were not significantly different from placebo: MK‐8998–placebo difference = −0.6 [95% confidence interval (CI): −7.0, 5.8], p = 0.9; olanzapine–placebo difference = −4.3 [95% CI: −11.7, 3.1), p = 0.3. A responder rate analysis (≥20% improvement from baseline in PANSS score) suggested an advantage of olanzapine over placebo (odds ratio = 2.20 [95% CI: 0.95, 5.09], p = 0.07) but no effect of MK‐8998 over placebo (odds ratio = 1.28 [95% CI: 0.62, 2.64], p = 0.5). Treatments were generally well tolerated, but more patients reported adverse events for MK‐8998 (47.7%) and olanzapine (48.9%) than placebo (37.3%). Conclusions: MK‐8998 was not effective in treating acutely psychotic inpatients with schizophrenia, as measured by PANSS score at week 4. Because of the limited efficacy of the active comparator, we cannot exclude the possibility that T‐type calcium channel antagonists could prove to be effective in schizophrenia. Copyright © 2013 John Wiley & Sons, Ltd.